Critical Limit of Soil and Plant Magnesium in Tomato-Growing Soils of South Karnataka - B L Kasinath (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2014)
Response of tomato to a blanket application of 50kg Mg ha-1 was studied at 20 locations on soil available Mg ranged from 40.6ppm to 172.4ppm. This range can be classified exchangeable Mg low to high status. These plots were selected from intensive tomato growing areas of southern Karnataka. The yield responses obtained from these plots were used to calculate the soil and plant Mg critical levels. Using scattered plot technique soil Mg limit of 74ppm is arrived as critical soil Mg for tomato crop. Similarly a plant critical limit of 0.39% was established to separate deficient plants from those having sufficient Magnesium.